Pengembangan Koleksi Perpustakaan Desa Kadujaya Jatidege Sumedang Jawa Barat sebagai Sumber Informasi Lingkungan - Rodiah, Saleha; Erwina, Wina; Prijana, Prijana; Nurislaminingsih, Rizki; Rahma , Silkvi Kheir (Media Pustakawan, 2025)
This research aims to develop the library collection according to the needs of the community to empower the community in information management. This research uses the Participatory Action Research method, which involves four research stages to identify the information needs of the village community. The stages are 1) Planning, 2) Action, 3) Observation, 4) Reflection. Data were collected through observation, in-depth interviews, documentation, and literature review. The research results show that at the planning stage, the people of Kadujaya village want an information centre in the form of a village library. Based on the discussion results, the researchers conducted an information mapping to determine the types of collections needed. The action stage was then carried out by procuring library collections through purchases and submitting proposals to relevant institutions, such as the National Library, BRIN, Taman Baca Arcamanik, and individuals. At the observation and reflection stage, the researchers found that the collection of the Kadujaya village library needs further development to ensure the diversity of information accessible to the community. The results of this study indicate that the development of the village library collection must be adjusted to the dynamics and evolving information needs of the community.